COMPARISION ANALYSIS OF NUMBER IN ENGLISH AND UZBEK LANGUAGES - Muxamadiyev A.SH.; Maxmanazarova Dilafruz Alisher qizi; Jumayeva Roza Yunus qizi (Лучшие интеллектуальные исследования, 2024)
Annotation: This article explores the similarities and differences in the category of numerals in Uzbek and English languages. The analysis focuses on the morphological features, syntactic functions, and semantic properties of numerals, as well as their role within the grammatical systems of these languages. The aim of the paper is to provide a deeper understanding of the category of numerals and to offer practical applications for teaching and learning.